KARAKTERISTIK DAN PERAN GURU DALAM PROSES BELAJAR SISWA - Winda Yanti Situmorang; Herti Yenisa Nainggolan; Niko Purba; Helena Turnip (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This article is based on the various characteristics of teaching staff or teachers in carrying out the teaching and learning process for students.  The role of teachers in the student learning process is very important. So the value of the influence of characteristics in a teacher needs to be considered, especially how teachers use their characteristics to motivate and encourage students in the continuation of the learning process. The aim of the research is to explore the characteristics of a professional teacher, so that they can influence students in the learning process. The method used is descriptive qualitative by analyzing and summarizing various opinions from books or journals from various experts regarding the characteristics of the teacher's role in supporting the student learning process. Understanding the various characteristics that exist in a teacher will help shape the characteristics of prospective teachers in understanding the relationship and role of teachers in the student learning process to answer the challenges of modern educational psychology, as well as improve the quality of the student learning process.